Utvärdering av stallpellets som strömaterial - Bengtsson, Jeanette; Martinell, Alexandra (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2016)
Humans have over time domesticated the horse from a wild animal into a domesticated. At first humans used horses to feed on, many years later they started to use horses as transportation and fighting gear. They also started housing the horses. Straw is one of the most common and cheapest bedding materials on the market. In earlier studies straw have shown a poor absorbency and high ammonia emission. The manufactures state that wood shaving pellets have a good absorption capacity and a low ammonia emission, there are few studies that supports this statement. The primary aim of this study was to evaluate wood shaving pellets, chopped straw and wood shavings on a daily base. The secondary aim was to calculate the economic factors on the different bedding materials. The study tested three bedding materials; wood shaving pellets, chopped straw and wood shavings. There were three groups of five to six horses in each group during five weeks of study. The experiment was located a stable at the Swedish National Equestrian Centre Strömsholm. The boxes were cleaned twice a day, once in the morning and once in the afternoon by the students in equine studies program. The working times of cleaning the boxes, manure discharge and adding fresh bedding materials were noted. Ammonia concentration was measured in each box at one time at the end of the study. A test was made to measure how many times each bedding material could absorb its own weight of water. The data were processed statistically and the significance level was set at p<0.05. An analysis of variance was done to find significant differences between treatments (bedding material) and where appropriate significant differences were followed with post-hoc test (Holm-Sidak). This study showed that wood shaving pellets was not profitable compared to chopped straw and wood shavings. The uppermost reason was the high purchase price, the material would be more profitable if the price was lower seeing that the material had the lowest working time, manure discharge and the lowest ammonia emission and should therefore be considered as a bedding material. Chopped straw was the bedding material that became most profitable due to the low purchase price, even though it had the highest working time and manure discharge. The studies first hypothesis “wood shaving pellets has a lower working time than wood shavings and chopped straw” was accepted. The other hypothesis “wood shavings is the most profitable bedding material” was rejected.